Manufacturing plant location selection in logistics network using Analytic Hierarchy Process - Ping-Yu Chang; Hsin-Yi Lin (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: In recent years, numerous companies have moved their manufacturing plants to China to capitalize on lower cost and tax. Plant location has such an impact on cost, stocks, and logistics network but location selection in the company is usually based on subjective preference of high ranking managers. Such a decision-making process might result in selecting a location with a lower fixed cost but a higher operational cost. Therefore, this research adapts real data from an electronics company to develop a framework that incorporates both quantitative and qualitative factors for selecting new plant locations. Design/methodology/approach: In-depth interviews were conducted with 12 high rank managers (7 of them are department manager, 2 of them are vice-president, 1 of them is senior engineer, and 2 of them are plant manager) in the departments of construction, finance, planning, production, and warehouse to determine the important factors. A questionnaire survey is then conducted for comparing factors which are analyzed using the Analytic Hierarchy Process (AHP). Findings: Results show that the best location chosen by the developed framework coincides well with the company's primal production base. The results have been presented to the company's high ranking managers for realizing the accuracy of the framework. Positive responses of the managers indicate usefulness of implementing the proposed model into reality, which adds to the value of this research. Practical implications: The proposed framework can save numerous time-consuming meetings called to compromise opinions and conflictions from different departments in location selection. Originality/value: This paper adapts the Analytic Hierarchy Process (AHP) to incorporate quantitative and qualitative factors which are obtained through in-depth interviews with high rank managers in a company into the location decision.
Keywords: 650; facility location; Analytic Hierarchy Process (AHP); supply chain management; delphi method; logistics network